URGENCY OF RECHTSVINDING AND JURISPRUDENCE IN THE CONSTITUTIONAL COURT AUTHORITY: URGENSI PENEMUAN HUKUM DAN YURISPRUDENSI DALAM KEWENANGAN MAHKAMAH KONSTITUSI - Imam Sujono (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
Indonesia is a democratic state based on the law (constitutional democratic state), with the understanding that the Constitution has a position as the supreme law because the whole administration of the state should be based on the Constitution. The Constitutional Court was present as the guardian of the constitution to the realization of the ideals of Indonesia as a democratic state based on law. The research entitled Rechtsvinding and Jurisprudence Used by the Constitutional Court examines the importance of rechtsvinding and the attachment of using jurisprudence in deciding cases according to the authority possessed by the Constitutional Court. This research uses the Socio-Legal method, which is a research method that examines a problem through normative analysis, then uses a non-legal science approach that develops in society. The results of the research that has been done are; 1 Rechtsvinding by the Constitutional Court interpreted as an effort to how the Constitutional Court interpreting the Constitution (1945), testing the laws against the 1945 Constitution, to decide the other cases the authority granted by the 1945 Constitution, 2) The Constitutional Court there is no obligation to be bound and is not there is a prohibition to use the jurisprudence of the Supreme Court.